Theoretical-conceptual, epistemic and methodological positions around the construct of integral human development (Revista Científica Compendium, 2023)
he search for the state of individual/social fullness and personal self-realization, have at the base of their operational foundation the tasks of integral human development, such as the process of continuous, dynamic, systematic growth as well as throughout the life cycle, that involves the expansion of possibilities in order to interact positively and coherently with the environment, in which the specification of opportunities and alternatives seeks to dignify life and existence as institutional responses. This research, as a result of a multidisciplinary documentary review, collects the theoretical-conceptual, epistemic and methodological positions around the construct of integral human development. It is concluded that the multidimensional growth of the individual depends on external and internal factors, from which to consolidate specific purposes such as: survival, the scope of success and the active willingness to participate jointly in the construction of enriching spaces focused on promoting the development of human capacities and individual/collective freedoms on which the functional balance of the subject depends.
Keywords: Integral Human Development; human capacities; individual/collective liberties; life dignity; multidimensional growth